Structural orientation dependent sub-lamellar bone mechanics. (December 2015) - Jimenez-Palomar, Ines; Shipov, Anna; Shahar, Ron; Barber, Asa H.
Abstract: The lamellar unit is a critical component in defining the overall mechanical properties of bone. In this paper, micro-beams of bone with dimensions comparable to the lamellar unit were fabricated using focused ion beam (FIB) microscopy and mechanically tested in bending to failure using atomic force microscopy (AFM). A variation in the mechanical properties, including elastic modulus, strength and work to fracture of the micro-beams was observed and related to the collagen fibril orientation inferred from back-scattered scanning electron microscopy (SEM) imaging. Established mechanical models were further applied to describe the relationship between collagen fibril orientation and mechanical behaviour of the lamellar unit. Our results highlight the ability to measure mechanical properties of discrete bone volumes directly and correlate with structural orientation of collagen fibrils. Highlights: A combination of SEM, AFM and FIB techniques were used to measure bone micromechanics. The relationship between bone micromechanics and collagen orientation was studied. There is a direct relationship between elastic modulus and mineralized collagen orientation. The results showed no correlation between elastic modulus with work-to-fracture.